VITAGEN TÁLIMDI ÁMELGE ASIRIWDÍŃ METODOLOGIYALÍQ TIYKARLARI - Dawletnazarova, D. (SCIENCE and SOCIETY, 2025)
This article discusses the methodological foundations for implementing and the principles of vitagenic education.